Positive priming effect explained by microbial nitrogen mining and stoichiometric decomposition at different stages. (December 2022) - Song, Xiaojun; Liu, Xiaotong; Liang, Guopeng; Li, Shengping; Li, Jingyu; Zhang, Mengni; Zheng, Fengjun; Ding, Weiting; Wu, Xueping; Wu, Huijun
Abstract: The priming effect is an essential mediator in the soil carbon (C) cycle. There is a growing concern about the priming effect induced by labile C input. However, the driving factors of the priming effect under agroecosystems with different historical tillage management remain unclear. By conducting a laboratory incubation experiment, the priming effect and the fate of 13 C-labeled glucose (1.658 atom%) were quantified in two soils (Cambisols and Phaeozems) that underwent the 12-year or 13-year tillage managements: rotary tillage without straw retention (RTN), and no-tillage with straw retention (NTS), and a grassland (GRL). After the 31-day incubation, RTN that had nitrogen (N) limitation emitted 26.7% more total C and 35.0% glucose-derived C than NTS across the two soil types. In Cambisols, the RTN exhibited 21.2% and 47.5% higher priming effect than NTS and GRL, respectively; while in Phaeozems, the RTN had 29.5% and 34.8% lower priming effect than NTS and GRL. Moreover, RTN showed 81.8% lower and 26.7% higher microbial C use efficiency (CUE) than NTS in Cambisols and Phaeozems, respectively. The higher N availability, CUE, and labile C retention which consists of the sum of glucose-derived microbial biomass C, total dissolved organic C, and organo-mineral C were the major contributors to the lower priming effect under long-term tillage management. A positive priming effect was observed across all treatments after glucose addition as a result of stimulating microbial activities, and then the increased microbial activities promoted co-metabolism. At the early stages, the priming effect was driven by "microbial N-mining", and the driving force was dominated by "microbial stoichiometric decomposition" at later stages. These findings provide a more accurate understanding of soil organic C dynamics. The results can be used to predict the change of soil organic C under long-term tillage management, which are critical for sequestrating the elevated atmospheric C concentrations. Highlights: The positive PE is caused by the microbial co-metabolism after glucose addition. The microbial mechanisms for PE at different stages are varied. Legacy effect of the long-term tillage management regulate CUE. Nutrient availability and CUE determine the magnitude of the PE.